2011
DOI: 10.1007/s11046-011-9441-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Genotype and Higher Virulence of a Strain of Sporothrix schenckii Causing Disseminated Cutaneous Sporotrichosis

Abstract: Sporotrichosis is usually a localized, lymphocutaneous disease, but its disseminated type was rarely reported. The main objective of this study was to identify specific DNA sequence variation and virulence of a strain of Sporothrix schenckii isolated from the lesion of disseminated cutaneous sporotrichosis. We confirmed this strain to be S. schenckii by(®) tubulin and chitin synthase gene sequence analysis in addition to the routine mycological and partial ITS and NTS sequencing. We found a 10-bp deletion in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…But in many different countries, lymphocutaneous form was the most commonly seen type, 21–26 although some other reports showed equal proportion of the two forms 16–17,27 . Possible causes for the different clinical forms include the size and depth of the inoculums, the genotype of the fungus, 28 and the immune status of the host 18 . Some authors thought 16,29 that the fixed cutaneous form reflects a higher immunity against S. schenckii , which could be acquired by frequent contact of fungal immunogen in a constantly endemic area.…”
Section: Discussionmentioning
confidence: 99%
“…But in many different countries, lymphocutaneous form was the most commonly seen type, 21–26 although some other reports showed equal proportion of the two forms 16–17,27 . Possible causes for the different clinical forms include the size and depth of the inoculums, the genotype of the fungus, 28 and the immune status of the host 18 . Some authors thought 16,29 that the fixed cutaneous form reflects a higher immunity against S. schenckii , which could be acquired by frequent contact of fungal immunogen in a constantly endemic area.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies [19] showed that the isolate (Sp98-12-1, i.e. DMU1) from disseminated sporotrichosis presented 10-bp deletion in the ribosomal nontranscribed spacer (NTS) region and higher virulence compared to the isolate (D1, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, sequences of S. schenckii s. str. were displayed across four clades: clade 1 showed a general topography in accordance with previous studies; clade 2 was formed mainly of Asian isolates including Malaysian sequences corresponding with Kano's group D, which was associated with cats disease and transmission; clade 3 comprised mostly Mexican sequences associated with transmission from the environment or small mammals; and clade 4 contained haplotypes from Africa, Argentina and Peru, and also associated predominantly with environmental transmission. In relation to S. globosa , two clades were seen.…”
Section: Resultsmentioning
confidence: 99%
“…These fungi are often introduced into the skin by traumatic injury involving soil, plants, or contaminated organic material or by animal contact . Lymphocutaneous nodules are the leading clinical manifestation, but localised and disseminated lesions have also been reported . In 2006, Sporothrix schenckii was proposed as a complex of cryptic species including medically relevant species such as S. schenckii sensu stricto (s.…”
Section: Introductionmentioning
confidence: 99%